Degradation of 17α-ethinylestradiol by nano zero valent iron under different pH and dissolved oxygen levels. (15th November 2017) - Karim, Sabrina; Bae, Sungjun; Greenwood, David; Hanna, Khalil; Singhal, Naresh
Abstract: The catalytic properties of nanoparticles (e.g., nano zero valent iron, nZVI) have been used to effectively treat a wide range of environmental contaminants. Emerging contaminants such as endocrine disrupting chemicals (EDCs) are susceptible to degradation by nanoparticles. Despite extensive investigations, questions remain on the transformation mechanism on the nZVI surface under different environmental conditions (redox and pH). Furthermore, in terms of the large-scale requirement for nanomaterials in field applications, the effect of polymer-stabilization used by commercial vendors on the above processes is unclear. To address these factors, we investigated the degradation of a model EDC, the steroidal estrogen 17α-ethinylestradiol (EE2 ), by commercially sourced nZVI at pH 3, 5 and 7 under different oxygen conditions. Following the use of radical scavengers, an assessment of the EE2 transformation products shows that under nitrogen purging direct reduction of EE2 by nZVI occurred at all pHs. The radicals transforming EE2 in the absence of purging and upon air purging were similar for a given pH, but the dominant radical varied with pH. Upon air purging, EE2 was transformed by the same radical species as the non-purged system at the same respective pH, but the degradation rate was lower with more oxygen – most likely due to faster nZVI oxidation upon aeration, coupled with radical scavenging. The dominant radicals were OH at pH 3 and O2 − at pH 5, and while neither radical was involved at pH 7, no conclusive inferences could be made on the actual radical involved at pH 7. Similar transformation products were observed without purging and upon air purging. Graphical abstract: Highlights: nZVI can remove EE2 in different removal mechanism at different pH and O2 conditions. Under N2 purging, nZVI directly reduces EE2 at pHs 3, 5, and 7. Under air- and non-purging, OH at pH 3 and O2 − at pH 5 caused EE2 degradation. Similar transformation products formed under air- and non-purging conditions. Faster nZVI oxidation occurred under the air purging condition.